Influence of the 2000-m ergometer test on indirect markers of intestinal injury in competitive elite rowers in different training phases - Dziewiecka, H.; Kasperska, A.; Ostapiuk-Karolczuk, J.; Cichon-Wozniak, J.; Basta, P.; Skarpanska-Stejnborn, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background We examined the effect of the 2000-m ergometer test on gut injury in competitive elite rowers in two different training phases. Given that inflammatory markers during the competitive phase are higher, we hypothesise that markers of intestinal injury are also more elevated during that phase.